2021
DOI: 10.1186/s12885-021-08974-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-immune profiling of CT-26 and Colon 26 syngeneic mouse models reveals mechanism of anti-PD-1 response

Abstract: Background Immune checkpoint blockade (ICB) therapies have changed the paradigm of cancer therapies. However, anti-tumor response of the ICB is insufficient for many patients and limited to specific tumor types. Despite many preclinical and clinical studies to understand the mechanism of anti-tumor efficacy of ICB, the mechanism is not completely understood. Harnessing preclinical tumor models is one way to understand the mechanism of treatment response. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 65 publications
(54 reference statements)
1
25
0
Order By: Relevance
“…The 4T1 and CT26 models are described to belong to tumors with differential immunoscore level. Indeed, the 4T1 model could be considered as a ‘cold’ phenotype with low response to immunotherapies [65] , despite the CT26 could be considered as a ‘hot’ phenotype with good response to immunotherapies [66] . Altogether these data might participate to explain the immunotherapy response observed in this work and in clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…The 4T1 and CT26 models are described to belong to tumors with differential immunoscore level. Indeed, the 4T1 model could be considered as a ‘cold’ phenotype with low response to immunotherapies [65] , despite the CT26 could be considered as a ‘hot’ phenotype with good response to immunotherapies [66] . Altogether these data might participate to explain the immunotherapy response observed in this work and in clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…Murine CT-26 cells, similar to human CRC cells, are massively invaded by TAMs and Tregs, which are associated with poor prognosis ( 51 ). In our study, we observed that neither a low dose of TPI nor IMQDC-Ag alone could induce ICD in vivo, whereas combination therapy did.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, existing pre-clinical models of human CRC that rely on syngeneic subcutaneous grafts are problematic because of increasing evidence that the immune microenvironment in subcutaneous tissue significantly differs from the gastrointestinal tract [ 70 ]. However, as shown by our study, the heterotopic syngeneic CT26 model, in addition to its use as a platform model for evaluating the efficacy of anti-cancer drug combinations, could also be used to assess phenotypic changes in the immune system [ 71 ]. Moreover, the resemblance of the CT26 models to the clinical observations of the response of CRC patients treated with immune checkpoint blockers further supports the relevance of the chosen model.…”
Section: Discussionmentioning
confidence: 99%